Assessing invasive alien aquatic plant species, phytoremediation effects using biological indicators in the Swartkops River system - Tshithukhe, Getrude (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2020)
Pollution effluents in freshwater ecosystems are becoming increasingly ubiquitous as a result of cumulative anthropogenic activities, such as wastewater treatments works, and industrial, agricultural and mining activities. These activities are more noticeable in urban river atchments where there is greater human population densities and industrial developments. The ecological effects of anthropogenic activities on freshwater ecosystems include: excessive deposition of contaminants such as nutrients, pharmaceuticals, microplastics and other chemicals, which change physicochemical properties, causing a decline in aquatic biodiversity. These effects, impact negatively on the resilience of freshwater, making the systems vulnerable to invasion by alien aquatic plants. Ultimately, the loss of local biodiversity associated with the invasive alien aquatic plants (IAAP) results in a loss of some ecosystem goods and services. The Swartkops River system, Eastern Cape Province, drains most of the neighbouring formal and informal settlements, agricultural lands and industries, and hence is exposed to water pollution from human activities along the river catchment. Various water quality assessments are needed to evaluate the extent of pollutants and their impacts on the river ecosystem. Phytoremediation is one approach employed internationally for removing harmful nutrients and chemicals in freshwater ecosystems. Most studies measure the success of phytoremediation through measuring the reduction of contaminants in water or soil chemistry in mesocosm settings, which may not take into account all the important environmental factors that exist in the field. The present study assesses the phytoremediation potential of Pontederia (Eichhornia) crassipes and Salvinia molesta by evaluating water and sediment chemistry, periphyton and aquatic macroinvertebrate community recovery along seven field sites (excluding IAAP species mats sites) located upstream and downstream IAAP species mats on the Swartkops River between April and September 2018. Water and sediment samples were collected once monthly on ten seven field sites, including the IAAP species mat sites. Periphyton and aquatic macroinvertebrates were collected on seven sites, excluding the IAAP mat sites. Pontederia crassipes and S. molesta infestation in Swartkops River showed positive phytoremediation results and improved some water and sediment chemistry in the downstream treatments as compared to upstream treatments. Although there were some fluctuations with some variables, important water and sediment chemistry were reduced downstream. By contrast, biological assessment results did not show any response to the presence of IAAP species and phytoremediation. Periphyton and aquatic macroinvertebrates diversity and community assemblages were more influenced by water quality. Although IAAP species did provide improvement in water and sediments chemistry, multiple effluent point and non-point sources in Swartkops outpaced phytoremediation. Taxa evenness and relative taxa abundance showed significant differences between the upstream and downstream sites, however taxa richness and Shannon's diversity showed no significant differences, indicating no relative recovery in biodiversity for either periphyton or aquatic macroinvertebrates. Similarly, the upstream and downstream sites showed similar periphyton and aquatic macroinvertebrates assemblages structure, all dominated by pollution tolerant taxa, thus indicating no functional diversity improvement down river; because of improvement in water chemistry downstream sites, it was expected that periphyton and aquatic macroinvertebrates assemblage structure would also improve at these downstream sites.It is possible that the phytoremediation process is outpaced by effluent discharges, given the multiple sources and distance between upstream and downstream mat sites. The study showed phytoremediation potential but the results were not indicated by biological indicators. A replica study conducted on a moderately disturbed river system is recommended to measure the success and recovery of biological indicators and assemblage composition following IAAP species phytoremediation; a moderately disturbed river compared to a largely disturbed river will broaden findings and look at differences for a wider application of phytoremediation.
Keywords: Aquatic weeds -- Biological control -- South Africa -- Eastern Cape; Alien plants -- Biological control -- South Africa -- Eastern Cape; Phytoremediation -- South Africa